Campus walkability: enhancing pedestrian safety through installation of raised crosswalks - Mohd Noor Azmi, A E; Daniel, B D (2023)
Walking is one of the most common sustainable modes of transportation in university campuses. To ensure its sustainability, pedestrian facilities that are safe, comfortable and reliable must be adequately provided. Various traffic calming measures have been introduced to enhance the safety of pedestrians. In Universiti Tun Hussein Onn Malaysia (UTHM), 6 raised crosswalks (RCW) have been installed along Persiaran Tun Ghafar Baba. This study aimed to investigate the impact of RCWs on vehicular speed reduction. Speed data were collected at each RCW. Vehicle speeds were recorded before, at and after the RCWs. Speed profiles developed indicate that the 85th percentile speed difference of RCWs were 14 – 25 km/h, which meant that the percentage of speed reduction at RCWs were remarkably high (31 – 48% reduction). Statistical tests confirmed that all RCWs yielded significant drops in speed i.e., the peak mean travelling speed versus the operational speed at the device. Furthermore, it was found that the zones of influence were between 29 – 50 m. This shows that drivers start reducing their speeds from as far as 50 m from the RCWs. Based on these findings, it can be concluded that raised crosswalks are effective in reducing speed, thus enhancing pedestrian safety while crossing as drivers tend to be more aware of their surroundings at lower speeds